Abusive supervision by academic supervisors and postgraduate research students' creativity: the mediating role of leader–member exchange and intrinsic motivation. Issue 5 (3rd September 2017) - Meng, Yi; Tan, Jing; Li, Jing
Abstract: Drawing upon the componential theory of creativity, cognitive evaluation theory and social exchange theory, the study reported in this paper tested a mediating model based on the hypothesis that abusive supervision negatively influences creativity sequentially through leader–member exchange (LMX) and intrinsic motivation. The study employed structural equation modelling to analyse data from a survey on 857 postgraduates with academic supervisors at four universities in China. The findings were that (1) LMX fully mediates the relationship between abusive supervision and intrinsic motivation; (2) intrinsic motivation partially mediates the relationship between LMX and creativity; and (3) LMX and intrinsic motivation sequentially mediate the relationship between abusive supervision and individual creativity. Theoretical contributions to understanding the mechanism underlying the effect of abusive supervision on individual creativity and the practical implications of academic supervisors' leadership practices and universities creativity management strategy are discussed.